Formas de participar: responsabilidade (com)partilhada entre escola e família na fala-em-interação social em contexto doméstico-familiar - Schnack, Cristiane Maria (Universidade do Vale do Rio dos Sinos, 2013)
Based on the theoretical and analytcal framework of the analysis of talk-in-interaction (SACKS, 1992; SACKS; SCHEGLOFF; JEFFERSON, 1974; C. GOODWIN, 1984) and of ethnomethodology (GRAFINKEL, 1967), this ethnographic study (O ́REILLY, 2009) aimed at understanding how two families, named as Catarina ́s family and Mila ́s family, which belong to different social classes, give meaning to their responsibilities concerning the school within the household environment while participanting in the child ́s school rotine. Responsibility originates from the responsive character of our actions (HILL; IRVINE, 1992), which thus qualifies it as intersubjective (OCHS; IZQUIERDO, 2009). The results point to distinct orientations in each family, named here as shared responsibility and divided responsibility. Shared responsibility evidences the centrality of the child and her school universe through the conarration of the child ́s school experiences, the coconstruction of a mutual understanding of the written world and script proposals (EMMISON et al., 2011) by the adults. They also share with school its pedagogical doings of mediating knowledge, through IRF sequences (COULTHARD; SINCLAIR, 1975; GARCEZ, 2006), constituting school and family as an extension of each other (CARVALHO, 2004). Divided responsibility, on the other hand, points to the pursuit of the child ́s autonomy concerning her school tasks and to the distinction between the school and the family ́s social nature, achieved through distribution, maintenance and the explicit negotiation of members ́s responsibilities (FINCH; MASON, 2006), and the crucial distinction between narrator and audience in narratives of school experience. Analyses also evidence the gendered constitution of fatherhood as encompassing the invisible work of organizing school at home (REAY, 2005) in Catarina ́s family, and motherhood as gatekeeper (GOTTZÉN, 2011) of the father ́s participation in Mila ́s family. This gendered work destabilizes normative discourses on paternal participation, especially in low income social classes, in which fathers are seen as managers of the household despite the fact that these households are, increasingly, being financially afforded by women (FONSECA, 2004). This study contributes to the understanding of family participation in the child ́s school trajectory as it proposes that participation is constitutive of the understanding families hold of their responsibilities towards the school, which ends up positioning the school either as a task to be performed or as a right to be offered to the child.
Keywords: Fala-em-interação; Relação escola-família; Participação familiar; Responsabilidade; Classe social; Talk-in-interaction; School-family relation; Family participation; Responsibility; Social class; ACCNPQ::Lingüística, Letras e Artes::Lingüística